2016
DOI: 10.5120/ijca2016912588
|View full text |Cite
|
Sign up to set email alerts
|

Congestion Control in MANET using Modify AODV with IRED Congestion Control Algorithm

Abstract: MANET is a field of networking that used for sharing of information between different links. In this process data has been transmitted from different devices to a single device to forward or store valuable information. Due to transmission of data from multiple sources to a single node occur congestion problem in the network. In this paper an approach has been proposed for congestion avoidance in MANET. This approach based on queue fulfillment prediction to avoid congestion and path management for data transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…TCP uses the AIMD clog control computation provided by sliding window design by Van Jacobson and others [1]. The field of network coding has seen a lot of research and development over the years, with several publications covering topics like coding strategies [3,4,5,6], network utility optimisation via network coding [7,8,9,10,11], and network coding implementation [12,14], among others. Since wireless channels are naturally broadcast and ideal for the application of network coding, the majority of the aforementioned studies are conducted through wireless networks.…”
Section: Working Of Tcpmentioning
confidence: 99%
See 1 more Smart Citation
“…TCP uses the AIMD clog control computation provided by sliding window design by Van Jacobson and others [1]. The field of network coding has seen a lot of research and development over the years, with several publications covering topics like coding strategies [3,4,5,6], network utility optimisation via network coding [7,8,9,10,11], and network coding implementation [12,14], among others. Since wireless channels are naturally broadcast and ideal for the application of network coding, the majority of the aforementioned studies are conducted through wireless networks.…”
Section: Working Of Tcpmentioning
confidence: 99%
“…The problem is that TCP has a hard time distinguishing between high traffic and a slow connection. This means that as long as there is no more data loss, the Transmission Control Protocol system will continue on the route to expansion in the window of congestion, so increasing the circulation frequency [9]. It's intriguing because of the potential for packet rejection due to congestion on the narrow channel.…”
Section: Present Weakness Of Tcpmentioning
confidence: 99%
“…this wireless agent in implemented in AODV protocol the result shows that there is the improvement in end to end delay , traffic load and high delivery ratio. KomalBadhran and Gautam Gupta [2] in this article the authors proposed the new protocol named wGDP which combines the congestion control and scheduling in MANET .This proposed protocol is using multicast algorithm which achieves the higher packet delivery and also reduced the overall overhead . S. Tamilselvi and O.P.UmaMaheshwari [3 ] , in this article authors uses the energy efficient algorithm implemented in Dynamic source routing protocol mechanism and simulation is done with the support of NS as a result shown that high level of energy is consumed but it improves the packet delivery ration and high network life time .…”
Section: Literature Survey Related To Congestion Controlmentioning
confidence: 99%